2021
DOI: 10.3389/fcimb.2021.766590
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of TLR4-Mediated Autophagy and Nitroxidative Stress

Abstract: Pathogenic infections have badly affected public health and the development of the breeding industry. Billions of dollars are spent every year fighting against these pathogens. The immune cells of a host produce reactive oxygen species and reactive nitrogen species which promote the clearance of these microbes. In addition, autophagy, which is considered an effective method to promote the destruction of pathogens, is involved in pathological processes. As research continues, the interplay between autophagy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 142 publications
0
18
0
Order By: Relevance
“…TLR4-mediated generation of oxidants and free radicals, especially ROS, (Ikram et al 2019;Park et al 2004;Sasaki et al 2008;Zhang et al 2021) represents a key event leading to oxidative stress and subsequent cell injury/apoptosis. Excessive ROS levels beget oxidative stress via several mechanisms, including inactivation of antioxidant defenses (Nrf2and Nrf-2-dependent factors HO-1, SOD2, and Catalase) (Bhattacharya 2015).…”
Section: Discussionmentioning
confidence: 99%
“…TLR4-mediated generation of oxidants and free radicals, especially ROS, (Ikram et al 2019;Park et al 2004;Sasaki et al 2008;Zhang et al 2021) represents a key event leading to oxidative stress and subsequent cell injury/apoptosis. Excessive ROS levels beget oxidative stress via several mechanisms, including inactivation of antioxidant defenses (Nrf2and Nrf-2-dependent factors HO-1, SOD2, and Catalase) (Bhattacharya 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first to reveal that activation of TLR4 and NFκB in lung tissues after SAH could be induced by the massive release of HMGB-1 from neuronal cells [ 23 ]. TLR4 has been demonstrated to trigger the activation of autophagy via a number of downstream signaling pathways, including TNF receptor-associated factor (TRAF)6, Toll/IL-1 receptor domain-containing adaptor interferon-B (TRIF), phosphatidylinositol 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) pathway, and the MyD88/NFκB pathway [ 24 ]. A previous in vitro study on macrophages identified TLR4 as a major trigger for LPS-induced proinflammatory cytokine release and autophagic activation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another crucial role of TOLLIP is the promotion of autophagy, which it facilitates by bridging ubiquitinated protein aggregates with LC3 and inhibiting the phosphorylation of vacuolar protein sorting 34 (VPS34), an important protein involved in autophagy [30]. Impaired autophagy and excessive ROS generation contribute to IPF progression.…”
Section: Discussionmentioning
confidence: 99%